2015
DOI: 10.1111/cns.12441
|View full text |Cite
|
Sign up to set email alerts
|

NFκB Signaling is Involved in the Effects of Intranasally Engrafted Human Neural Stem Cells on Neurofunctional Improvements in Neonatal Rat Hypoxic–Ischemic Encephalopathy

Abstract: Intranasal delivery of hNSCs could prevent HI-induced brain injury and improve neurobehavioral outcomes in neonatal HI rats, which is possibly related to the modulation of NF-κB signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Several studies have demonstrated that intranasal stem cells treatment improves sensorimotor and cognitive function, and decreases gray or white matter damage after HI [37-39]. In our present study, CM-Dil staining was used to label and track the migration of NSCs.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have demonstrated that intranasal stem cells treatment improves sensorimotor and cognitive function, and decreases gray or white matter damage after HI [37-39]. In our present study, CM-Dil staining was used to label and track the migration of NSCs.…”
Section: Discussionmentioning
confidence: 95%
“…Based on our present study, we concluded that the autophagy was reduced in diabetic mice. Previous studies found that Akt plays a role in induced endothelial injury in diabetes [31], and that the NF-kB pathway is a mechanism of cerebral ischemia and hypoxia [51]. Next step, we will explore whether Akt and NF-kB pathway has an effect on diabetic cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…hours or up to several days, within the nasal cavity [ 44 , 50 ] which is highly equipped with immunocompetent cells due to continuous exposure to antigenic stimuli. However, this notion is counterbalanced by the fact that human MSC and NSC can reach the brain after intranasal administration in immunocompetent rodent models of brain disorders [ 12 , 51 ]. Moreover, intranasally administered human MSC derived from clinical-grade human iPSC line were shown to provide greater protection than corticosteroids against allergic airways disease in mice [52] .…”
Section: Discussionmentioning
confidence: 99%